Effects of coated urea fertilizers on growth and yield of MR219 rice (Oryza sativa L.) - A. Rahman, Nur Syamimi (2016)
Urea is widely used as a nitrogen fertilizer. However, the efficiency of urea is generally low due to the rapid hydrolysis which has resulted in the low N uptake and contributed to the hazardous environmental effect. The improvement in urea efficiency can be achieved by coating the urea with selected coating materials. The coated fertilizer is known as a slow release fertilizer which ultimately can reduce fertilizer consumption and minimize the environmental pollution. Experiments were conducted under laboratory incubation and glass-house conditions with the following objectives (i) to determine the losses of nitrogen from urea coated fertilizers via ammonia volatilization and nitrogen mineralization, (ii) to determine the growth performance and yield of Oryza sativa (MR219) in response to various dosages of urea coated fertilizers. The optimization of the rate and the time of N fertilizer application as well as investigation of different N fertilizer formulation were conducted to determine the effects of these parameters on growth performance in terms of N release in accordance to the rice plant requirement. The incubation studies were conducted to investigate nitrogen losses via ammonia volatilization and mineralization (nitrate leaching). The fertilizers labeled as uncoated urea (U), sulfur coated urea (SCU), gypsum and sulfur coated urea using rotating drum (GSCUD). The rates of fertilizer used were 50, 100, and 200 kg N/ha. The results revealed that sulfur coated urea (SCU) was the best fertilizer since it reduced the rate of ammonia volatilization followed by GSCU and U. The ammonium and nitrate accumulations were also studied using the same nitrogen fertilizers including control (no fertilizer added) at 100 kg N/ha. Coating the urea with either 100% sulfur as in the commercial SCU or 50:50 ratio of gypsum and sulfur in GSCUD demonstrated the reduction in urea losses via both ammonia volatilization and nitrate leaching. As much as 25% reduction in ammonia losses via volatilization was observed using SCU and 14% using GSCUD. The results from this study also showed that the losses via nitrate in solution are relatively lower compared to ammonium in solution (4.35 mg/L compared to 0.73 mg/L). The effects of three fertilizers (Urea, SCU, GSCUD) using five rates (0, 50, 100, 150, 200 kg N/ha) and two times of application (single application at 25 DAT (Day after Planting) and two times application at 25, and 55 DAT) were evaluated under glass-house conditions. The plants were harvested at 120 DAT. A glass-house study of first planting showed that fertilizer with a single application at the rate of 100 kg N/ha showed acceptable plant growth performance in terms of vegetation and yield parameters particularly for GSCUD fertilizer. Using GSCUD (100 kg N/ha with single application) resulted in 100 grain weight of 4.21 g/pot compared to the other treatments. However, as expected two times of application showed higher productivity. Using GSCUD (two-times; 200 kg N/ha) gave higher plant biomass 65.43 g/pot and markedly higher in grain yield at 39.52 g/pot. Moreover, the highest level for two-times application increased the uptake of nitrogen by plant up to 52.55 g/pot for the treatment using GSCUD. The second planting was also carried out under glass-house condition, to repeat the earlier glasshouse experiments and adding few other new coated fertilizers. The rate of application was at 100 kg N/ha, single application. Six different types of fertilizers were tested, namely U, SCU, GSCUP (gypsum and sulfur coated urea using rotating pan), GSCUD (gypsum and sulfur coated urea using rotating drum), DCU (dolomite coated urea), and KCU (kaolinite coated urea). The outcomes showed that the application of DCU to the crop improved the growth as well as the productivity of the rice yield. The use of DCU increased the plant biomass to 31.60 g, grain yield at 14.84 g/pot and higher in nitrogen uptake at a 16.36 g/pot. The next best fertilizers were GSCUD and KCU fertilizer. The grain yield was 13.01 g/pot and 13.31 g/pot, plant biomass at 34.96g and 24.82g, and nitrogen uptake 14.65 g/pot and 13.83 g/pot, respectively.